Деякі аспекти формування сучасного економічного механізму управління транспортною складовою житлово-комунального комплексу регіону - Кириченко, О.І. (Культура народов Причерноморья, 2012)
В даній статті дається обґрунтування того факту, що в сучасних умовах господарювання
на регіональному рівні питання реформування транспортної інфраструктури житлово-комунального
комплексу (далі ЖКК) є одним з першочергових. На основі існуючих досліджень і розробок як
вітчизняних, так і зарубіжних вчених пропонується авторський алгоритм побудови прикладного
адаптивного механізму удосконалення економічного механізму управління транспортом в рамках ЖКК з
використанням передових технологій оптимізації організаційної структури системи транспорту.
Ключові слова: транспортна система житлово-комунального комплексу, економічний механізм,
реформування, аутсорсинг, стратегічне управління, регіональний стандарт ефективності. В данной статье обоснован тот факт, что в современных условиях хозяйствования на
региональном уровне вопросы реформирования транспортной инфраструктуры жилищно-
коммунального комплекса (далее ЖКК) являются одними из первоочередных. На основе существующих
исследований и разработок как отечественных, так и зарубежных ученых предлагается авторский
алгоритм построения прикладного адаптивного механизма усовершенствования экономического
механизма управления транспортом в рамках ЖКК с использованием передовых технологий
оптимизации организационной структуры системы транспорта.
Ключевые слова: транспортная система жилищно-коммунального комплекса, экономический механизм,
реформирование, аутсорсинг, стратегическое управление, региональный стандарт эффективности. In this article there is a substantiation of the fact that in modern conditions of managing at regional
level issues of transport infrastructure, as a part of housing-and-municipal complex reforming, are ones of
prime. On the basis of existing researches and developments, made by both - domestic and foreign scientists -
the author's algorithm of applied adaptive mechanism’s of transport within housing-and-municipal complex
creation, with use of advanced technologies of the transport infrastructures organizational structure’s
optimization, is offered. Development of the noted algorithm is based on determination of composition
programmatic-aming and normative-aming blocks and analysis of connections between them. Program-aming
(PA) block is related to the strategic planning, which carries perspective character of influence on the solving of
transport problems. Appliance of normative-aming (NA) block is related to development of a regional transport
standard of efficiency, which reflects satisfaction of demand in high-quality services of carrying passengers and
loads.
Key words: transport system of housing-and-municipal complex, economic mechanism, reforming, outsourcing,
strategic management, regional standard of efficiency.